A V4 országok versenyképességének alakulása, kitekintéssel a Kínával való gazdasági kapcsolatokra: THE DEVELOPMENT OF V4 COUNTRIES’ COMPETITIVENESS, WITH AN OUTLOOK ON ECONOMIC RELATIONS WITH CHINA - Gergics, Tünde; Huszti, Réka; Schwertner, Marcell (Közép-Európai Közlemények, 2019)
One of the main directions of this study is the examination of the economic development and competitiveness of the Visegrad countries since the 2000s. From the turn of the millennium, development has entered a new phase that visibly shapes the former fields of power in the region and creates new geopolitical focal points. In this rearrangement, different economic processes play a key role. Although the development of the countries of the Visegrad Group is homogenous - partly due to the common historical past - has, in many respects, varied in some of its features. However, the analysis of the V4 countries, due to the above-mentioned homogeneity and central geographical location, is appropriate subject of examination to draw conclusions for the situation in the Central and Eastern European region. Following the 2008 global economic crisis, China’s economic development and global political expansion has entered a new phase. The effect of this phenomenon is exerted on the geopolitical field. The New Silk Road Program announced by the Chinese government in 2013 is of paramount importance for the future of the Central and Eastern European region. The new commercial opportunities and potential FDI investments resulting from the program are desirable for the entire Visegrad Group. In the course of our study, we intend to include several indicators that better illustrate and measure the economic strategy and geopolitical changes of the period 2004-2015 in the V4 countries, with a special view on economic relations with China. Jelen tanulmány egyik fő irányvonala a Visegrádi Együttműködés országainak gazdasági fejlődésének vizsgálata a 2000-es évektől. Az ezredfordulótól a fejlődés egy olyan új szakaszba lépett, amely láthatóan formálja a térség korábbi erőtereit és új geopolitikai súlypontokat hot létre. Ebben az átrendeződésben a különböző gazdasági folyamatoknak kiemelt szerepük van. Habár a Visegrádi országok gazdasági fejlettsége homogénnek mondható – részben a közös történelmi múlt miatt – azonban számos jellemzőben eltérést mutat. Ennek ellenére a V4 országok – az említett homogenitás, illetve a hasonló központi földrajzi fekvés miatt – megfelelő vizsgálati alapot nyújtanak a kelet-közép-európai régiós helyzet feltérképezésében. A 2008-as világgazdasági válságot követően a kínai gazdasági fejlődés, világpolitikai térnyerés új fázisba lépett. Ennek a jelenségnek a fokozott hatása érvényesül a geopolitikai erőtérre. A kínai kormányzat által 2013-ban meghirdetett Új Selyemút program rendkívüli jelentőséggel bír a kelet-közép-európai térség jövője szempontjából. A programból fakadó új kereskedelmi lehetőségek és potenciális FDI befektetések kiaknázása pedig a teljes Visegrádi csoport számára kívánatos. A vizsgálatunk során több indikátort kívánunk bevonni, amik jobban bemutatják és mérik a 2004-2015 közötti időszak gazdaságstratégiai és geopolitikai változásait a V4 országokban, külön kitekintéssel a Kínával való gazdasági kapcsolatokra.